The Depiction of Okonkwo's Tragic Situation through Symbols: An Analysis of Achebe's Things Fall Apart - Surendra Prasad Ghimire (PT FORMOSA CENDEKIA GLOBAL, 2023)
This paper aims to investigate how Achebe utilized various symbols to project the protagonist, Okankow's, forthcoming tragic situation in the novel Things Fall Apart. I utilized the concept of the symbol as a theoretical perspective to analyze the text. Here, I argued that Achebe used various symbols in the novel to reflect the protagonist's forthcoming devastating situation. The discussion has identified that Achebe used multiple symbols, such as Okonkwo's involvement in killing Ikemefuna, Ezeudu's son, ash, fire, and so forth, which symbolized Okonkwo's forthcoming devastating situation. The findings of this study contribute to a better understanding of the role of symbols in projecting the forthcoming tragic condition in the life of protagonist Okonkwo and provide a clear direction for further exploring the role of symbols in Achebe's novel Things Fall Apart